Simultaneous Bacillus anthracis Spores Detection via Aminated-Poly(vinyl chloride) Coated Piezoelectric Crystal Immunosensor. (19th August 2014) - Oztuna, Ali; Nazir, Hasan; Baysallar, Mehmet
Abstract : Bacillus anthracis spores are a potential threat to countries in the context of biodefense. We have already seen the destructiveness of the anthrax attacks in the recent past. This study presents an aminated-poly(vinyl chloride) (PVC-NH2 ) coated quartz crystal microbalance (QCM) immunosensor for simultaneous rapid detection of B. anthracis spores. PVC-NH2, synthesized in the laboratory, was used as an adhesive layer for monoclonal antibody immobilization on gold quartz crystal. The prepared QCM sensor was tested using a pathogen field strain of B. anthracis (GenBank number: GQ375871.1) under static addition and flow through procedures with different spore concentrations. Fourier transform infrared spectroscopy (FTIR-ATR) and scanning electron microscopy (SEM) were performed to characterize the surface of the sensor during the modification. Furthermore, a series of SEM micrographs were taken in order to investigate surface morphology and show the presence of the B. anthracis spores on the surface. It is concluded that B. anthracis spores can be accomplished by using amine functionalized polymer coated QCM sensors without requiring complicated immobilization procedures or expensive preliminary preparations.